Taste coding in the parabrachial nucleus of the pons in awake, freely licking rats and comparison with the nucleus of the solitary tract - Weiss, Michael S. (American Physiological Society, 2013)
In the rodent, the parabrachial nucleus of the pons (PbN) receives information about taste directly from the nucleus of the solitary tract (NTS). Here we examined how information about taste quality (sweet, sour, salty, and bitter) is conveyed in the PbN of awake, freely licking rats, with a focus on how this information is transformed from the incoming NTS signals. Awake rats with electrodes in the PbN had free access to a lick spout that delivered taste stimuli (5 consecutive licks; 100 mM NaCl, 10 mM citric acid, 0.01 mM quinine HCl, or 100 mM sucrose and water) or water (as a rinse) on a variable-ratio schedule. To assess temporal coding, a family of metrics that quantifies the similarity of two spike trains in terms of spike count and spike timing was used. PbN neurons (n = 49) were generally broadly tuned across taste qualities with variable response latencies. Some PbN neurons were quiescent during lick bouts, and others, some taste responsive, showed time-locked firing to the lick pattern. Compared with NTS neurons, spike timing played a larger role in signaling taste in the first 2 s of the response, contributing significantly in 78% (38/49) of PbN cells compared with 45% of NTS cells. Also, information from temporal coding increased at a faster rate as the response unfolded over time in PbN compared with NTS. Collectively, these data suggest that taste-related information from NTS converges in the PbN to enable a subset of PbN cells to carry a larger information load.